Pattern formation in terms of semiclassically limited distribution on lower dimensional manifolds for the nonlocal Fisher–Kolmogorov–Petrovskii–Piskunov equation - Levchenko E. A. Evgeny Anatolievich (2013, 2013)
Title screen